2003
DOI: 10.1124/jpet.103.058073
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Effects of FK419, a Novel Nonpeptide Platelet GPIIb/IIIa Antagonist, in a Guinea Pig Photochemically Induced Middle Cerebral Artery Thrombosis Model: Comparison with Ozagrel and Argatroban

Abstract: Platelet activation and subsequent aggregation play a key role in the pathogenesis of ischemic brain damage. Recent studies revealed that enhanced platelet activation is also observed after ischemia, suggesting that secondary thrombus formation might participate in the development of cerebral infarction. The binding of platelet glycoprotein GPIIb/IIIa (integrin ␣ IIb ␤3) to fibrinogen is the final common pathway in platelet aggregation. Therefore, GPIIb/IIIa antagonists might be useful in acute ischemic stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…FK419 significantly improved both MCA patency and ischemic brain damage, whereas rt-PA improved MCA blood flow but minimally improved neurologic deficits and caused petechial intracerebral hemorrhaging. We recently reported that FK419 dose-dependently prevented the reocclusion of MCA after recanalization in photothrombotic MCA occlusion model in guinea-pigs (Moriguchi et al , 2004 a ). FK419 was found not only to prevent reocclusion but also to thrombolyse the obstructive thrombus in a similar model (Moriguchi et al , 2004 b ; Moriguchi et al , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…FK419 significantly improved both MCA patency and ischemic brain damage, whereas rt-PA improved MCA blood flow but minimally improved neurologic deficits and caused petechial intracerebral hemorrhaging. We recently reported that FK419 dose-dependently prevented the reocclusion of MCA after recanalization in photothrombotic MCA occlusion model in guinea-pigs (Moriguchi et al , 2004 a ). FK419 was found not only to prevent reocclusion but also to thrombolyse the obstructive thrombus in a similar model (Moriguchi et al , 2004 b ; Moriguchi et al , 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The left MCA was photochemically occluded according to the method of Moriguchi et al (2004a,b). Briefly, animals were anesthetized with isoflurane (2% for induction, 1% for maintenance) in a mixture of air and 30% O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This model involves a photochemical reaction between rose bengal and transluminal light irradiation, leading to endothelial injury followed by platelet adhesion, aggregation, and a formation of occlusive platelet-rich thrombus at the irradiated site (Saniabadi et al , 1995). FK419 improved brain damage not only by preventing reocclusion of MCA but also by lysing the obstructive thrombus in both the guinea-pig and primate photochemical thrombosis model (Moriguchi et al , 2004a,b; Maeda et al , 2005). FK419 showed a superior profile in the MCA thrombosis models compared with that of common antithrombotic agents, including recombinant tissue plasminogen activator, aspirin, ozagrel, heparin, and argatroban.…”
Section: Introductionmentioning
confidence: 99%
“…Its mechanism is to inhibit the biosynthesis of thromboxane A 2 from arachidonic acid in platelets through acetylation of the crucial enzyme: cyclooxygenase. Though specific inhibitors of the thromboxane A 2 , thromboxane synthase and the enzyme have been developed, these drugs reduce prostaglandin I 2 production in the endothelium, which may lead to the decreasing of cerebral blood flow [7].…”
Section: Antiplatelet Therapymentioning
confidence: 99%